Transformation Of IAIN Into UIN And Internal Supervision Unit Model - Erwin Erwin; Nasfi Nasfi (International Journal of Islamic Business and Management Review, 2022)
National Islamic Religious Universities (PTKIN) have begun to change their form, thus a supervisory step is needed in the form of an Internal Supervisory Unit (SPI) in accordance with the Regulation of the Minister of Religion of the Republic of Indonesia No. 25 of 2017. Where the PTKIN supervision system is required to focus on achieving Governance, control, risk management, but not just administrative activities. The steps and the presence of SPI in PTKIN are required by all elements to understand and share views on how the duties and responsibilities of SPI are, no less important is the leadership of PTKIN to the highest decision maker or top management. The research was conducted at 3 (three) PTKIN which will be transformed into a State Islamic University (UIN) using the "A Case Study" method. Data obtained from interviews, observations and documentation then processed. Processing of data by checking the correctness of the data, compiling data, carrying out coding, classifying data, correcting unclear interview answers. The results of the research on the implementation of internal control at PTKIN are running, but there are still aspects of supervision that have not been fully implemented. Steps to increase supervision by increasing the number of SPI personnel and adding supporting tools such as an integrated information system. The goal is that the implementation of Governace in SPI reaches all aspects of activities in the work unit, so that the supervision system runs fully.